1989
DOI: 10.1248/cpb.37.2406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activities of alkyl-1,4-butanediamine Pt(II) complexes having seven-membered ring structure.

Abstract: Novel alkyl-1,4-butanediamine Pt(II) complexes having a seven-membered ring structure were synthesized and characterized by fast atom bombardment mass and infrared spectra and elemental analysis. Their antitumor activities in vivo toward lymphoid leukemia L1210 and Lewis lung carcinoma LL were studied in the case where the leaving group was either dichloride or cyclobutane-1,1-dicarboxylate. 1,4-Butanediamine Pt(II) complexes (seven-membered ring) showed higher antitumor activities than those of ethylenediamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The synthesis of the diiodo platinum compounds for the other diamines was performed by using K 2 PtI 4 [11][12][13][14][15]. This compound was prepared in situ starting from K 2 PtCl 4 and a large excess of potassium iodide.…”
Section: Synthesis Of Platinum(ii) Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of the diiodo platinum compounds for the other diamines was performed by using K 2 PtI 4 [11][12][13][14][15]. This compound was prepared in situ starting from K 2 PtCl 4 and a large excess of potassium iodide.…”
Section: Synthesis Of Platinum(ii) Complexesmentioning
confidence: 99%
“…Thus, for the series 12-15, there are interesting differences in the circular dichroism behaviour between the compounds with a double bond (14,15) and the compounds with the aliphatic or aromatic ring (12,13). For the compounds with a substituent on the C-3 position, there is a wide variety of behaviours: (a) Among the methoxylated complexes, differences between the compounds with and without a double bond were observed, and (b) The compounds 16 and 17 having C@C double bond also showed differences in the ellipticity, indicating that the ligand configuration may affect the interaction of the molecule of complex with DNA at this level.…”
Section: Circular Dichroismmentioning
confidence: 99%
See 1 more Smart Citation
“…6 1,4-Butaneamine, expressed as R in the text, has disagreeable odor, which is a toxic diamine formed by putrefaction from the decarboxylation of arginine and ornithine. It is a good ligand used to prepare Pt(II), Pt(IV) complex, 7 which have an anti-cancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…This point of view leads to the design of antitumor drugs focusing mainly on the chirality of the carrier ligand. [32][33][34][35][36] The complexes with diamines of R or RR absolute configuration are slightly more active than the complexes with the corresponding diamines owning S, SS or RS configuration. 37 The study of four optical isomers of (mandelato)(trans-1,2-diaminocyclohexane)platinum(II) compounds indicated that the chiralities of both carrier ligands and leaving groups affect the antitumor activities of the complexes.…”
mentioning
confidence: 99%